(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the effect of capital structure, company size, profitability, and investment opportunity set on earnings quality. The population in this study is pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2024. The sample used in this study is a purposive sampling method. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX). The analysis technique used is multiple linear regression analysis using SPSS version 25. The partial results of the study indicate that: Capital structure has a negative effect on earnings quality. Company size does not affect earnings quality. Profitability has a positive effect on earnings quality. Investment opportunity set does not affect earnings quality. Meanwhile, the simultaneous results show that capital structure, company size, profitability, and investment opportunity set affect earnings quality. The R Square value is 0.437, which means that the independent variables together can influence the Earnings Quality variable by 43.7%, the remaining 56.3% comes from other variables outside the variables of this study.